The impact of international investment agreements on FDI in developing countries and the implications for development policy - Lomas, Djamella (Rhodes University, Faculty of Commerce, Department of Economics and Economic History)
This study investigates the impact of international investment agreements, specifically bilateral investment treaties (BITs), on inward Foreign direct investment (FDI) in recipient developing countries and the implications of such agreements for development policy. The study estimates a log-linear gravity model based on a unique dataset created to investigate whether the presence of BITs has a positive impact on inward FDI stock in 36 developing countries. The selection of countries attempts to capture a set of bilateral relationships that accounts for a significant proportion of inward FDI in developing countries. To test the hypothesis that signing BITs has a positive effect on inward FDI in developing countries it was necessary that all recipient countries be developing economies. However, investor countries are both developed and developing economies. Therefore, each bilateral FDI relationship is either between a developing recipient and developed investor country or between a developing recipient and developing investor country. For each recipient country, FDI stock data from investor countries for 2019 was obtained from the ITC's Investment Map database (ITC, 2022). This yielded 1009 bilateral FDI relationships (observations for the dependent variable) after removing pairs for which certain explanatory variable data was not available. For the gravity model, GDP data was collected from the World Bank's World Development Indicators Database (World Bank, 2023a), while the other traditional gravity variables were collected from the CEPII GeoDist Database (CEPII, 2011). Alongside the gravity variables, the study employs three additional control variables (two macroeconomic and one institutional) in certain specifications of the basic model, namely the exchange rate, inflation rate and an index of political stability. Data for the three additional variables was sourced from the IMF's World Economic Outlook Database (IMF, 2022) for the macroeconomic variables and the World Bank's Worldwide Governance Indicators Database (World Bank, 2023b) in the case of the political stability index. To examine the key question of the impact of BITs on bilateral FDI, a number of BITs dummy variables are created to investigate, firstly, whether having signed a BIT impacts on FDI in developing countries and, secondly, whether having a BIT in force significantly impacts on FDI in developing countries. Thereafter, in each case, dummy variables are created to investigate whether there is a significant difference between the impact on FDI of having a BIT signed or in force between a developed and developing country specifically, and having a BIT signed or in force between two developing countries. In order to examine the implications for development policy, the thesis analyses case studies of selected BITs between developed and developing economies, as well as those between developing economies. The texts of the BIT documents were obtained from the UNCTAD Investment Policy Hub Database (UNCTAD, 2023b). The results of the study reveal that, on average, signing and/or having a BIT in force has a significant positive impact on the inward FDI stock of the recipient developing country from the outward investor country. This positive impact is found to be even stronger in the case of BITs between developed and developing countries. However, there is no significant impact on inward FDI for BITs signed between two developing countries. The study finds that GDP of the recipient and investor country, existence of a common official language and the distance between countries all have a significant impact on FDI in the recipient developing country, and are signed as expected in the gravity literature. The existence of a common border is weakly significant in some specifications of the basic model and not significant in others. The additional control variables are all significant and signed as expected in the literature. The study contributes to the literature by distinguishing, not only between the impact of BITs signed versus BITs in force on inward FDI in developing countries, but also by distinguishing between the impact of BITs on FDI when the partners are developed and developing countries versus when both partners are developing countries. The study also finds that, in an effort to attract FDI, developing countries have signed BITs which carry obligations that extend significant protection measures to foreign investors. However, such protections are offered at the expense of sovereign interests. The study finds that this has served to significantly reduce the policy space available for developing countries to attract FDI that is aligned to their sustainable development needs. The limitations of the study are as follows. The gravity specification is cross-sectional, and a panel data approach could be recommended for future work. Furthermore, the traditional OLS gravity specification has a number of disadvantages and different types of estimator could be used in future work, software permitting. In addition, the impact on FDI of the termination of BITs could be investigated, as sufficient data is becoming available for such an approach. Finally, it is difficult to generalise from the case study analysis undertaken of specific BITs provisions because of the limited number of BITs examined in the thesis.
Keywords: Investments, Foreign; Bilateral Investment Treaty; Gravity model of international trade; Developing countries -- Foreign economic relations; Developing countries -- Economic policy; BRIC countries